Financial Sector Assessment : Turkey - World Bank; International Monetary Fund (World Bank, Washington, DC, 2017)
The fundamental challenges confronting the Turkish financial system are to reduce dependence on external and foreign currency financing and to increase the maturity and diversity of funding instruments on which banks and firms depend. The long-standing shortfall of national savings to finance domestic investment, persistent elevated inflation, and bouts of exchange rate volatility have boosted reliance on foreign currency financing from international capital markets and have also incentivized households and firms to place their own savings in short term deposits, as well as in foreign currency. These deep-seated challenges underpin current heightened financial stability risks from several potential sources -—tighter or more volatile global funding conditions, weaker euro area growth, geo-political tensions and loss of market confidence in domestic policies. Balance-sheet fragilities could amplify their impact.